Curcumin supplementation could improve diabetes-induced endothelial dysfunction associated with decreased vascular superoxide production and PKC inhibition - Ruangvejvorachai Preecha; Thenchaisri Naris; Rungseesantivanon Sirada; Patumraj Suthiluk (BMC, 2010)
Abstract Background Curcumin, an Asian spice and food-coloring agent, is known for its anti-oxidant properties. We propose that curcumin can improve diabetes-induced endothelial dysfunction through superoxide reduction. Methods Diabetes (DM) was induced in rats by streptozotocin (STZ). Daily curcumin oral feeding was started six weeks after the STZ injection. Twelve weeks after STZ injection, mesenteric arteriolar responses were recorded in real time using intravital fluorescence videomicroscopy. Superoxide and vascular protein kinase C (PKC-βII) were examined by hydroethidine and immunofluorescence, respectively. Results The dilatory response to acetylcholine (ACh) significantly decreased in DM arterioles as compared to control arterioles. There was no difference among groups when sodium nitroprusside (SNP) was used. ACh responses were significantly improved by both low and high doses (30 and 300 mg/kg, respectively) of curcumin supplementation. An oxygen radical-sensitive fluorescent probe, hydroethidine, was used to detect intracellular superoxide anion (O2●-) production. O2●- production was markedly increased in DM arterioles, but it was significantly reduced by supplementation of either low or high doses of curcumin. In addition, with a high dose of curcumin, diabetes-induced vascular PKC-βII expression was diminished. Conclusion Therefore, it is suggested that curcumin supplementation could improve diabetes-induced endothelial dysfunction significantly in relation to its potential to decrease superoxide production and PKC inhibition.